Effects of Yulin Tong Bu formula on modulating gut microbiota and fecal metabolite interactions in mice with polycystic ovary syndrome - Su, Ya-Nan; Wang, Mei-Jiao; Yang, Jun-Pu; Wu, Xiang-Lu; Xia, Min; Bao, Mei-Hua; Ding, Yu-Bin; Feng, Qian; Fu, Li-Juan (Frontiers in Endocrinology, 2023)
Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder characterized by hyperandrogenism, ovarian dysfunction and polycystic ovarian morphology. Gut microbiota dysbiosis and metabolite are associated with PCOS clinical parameters. Yulin Tong Bu formula (YLTB), a traditional Chinese medicine formula, has been recently indicated to be capable of ameliorating polycystic ovary symptoms and correcting abnormal glucose metabolism. However, the therapeutic mechanism of YLTB on PCOS has not been fully elucidated. Methods: A pseudo sterile mouse model was established during this four-day acclimatization phase by giving the animals an antibiotic cocktail to remove the gut microbiota. Here, the therapeutic effects of YLTB on PCOS were investigated using dehydroepiandrosterone plus high-fat diet-induced PCOS mice model. Female prepuberal mice were randomly divided into three groups; namely, the control group, PCOS group and YLTB (38.68 g·kg-1·day-1) group. To test whether this effect is associated with the gut microbiota, we performed 16S rRNA sequencing studies to analyze the fecal microbiota of mice. The relationships among metabolites, gut microbiota, and PCOS phenotypes were further explored by using Spearman correlation analysis. Then, the effect of metabolite ferulic acid was then validated in PCOS mice. Results: Our results showed that YLTB treatment ameliorated PCOS features (ovarian dysfunction, delayed glucose clearance, decreased insulin sensitivity, deregulation of glucolipid metabolism and hormones, etc) and significantly attenuated PCOS gut microbiota dysbiosis. Spearman correlation analysis showed that metabolites such as ferulic acid and folic acid are negatively correlated with PCOS clinical parameters. The effect of ferulic acid was similar to that of YLTB. In addition, the bacterial species such as Bacteroides dorei and Bacteroides fragilis were found to be positively related to PCOS clinical parameters, using the association study analysis. Conclusion: These results suggest that YLTB treatment systematically regulates the interaction between the gut microbiota and the associated metabolites to ameliorate PCOS, providing a solid theoretical basis for further validation of YLTB effect on human PCOS trials.